Identifikasi Keragaman SNP Gen MSTN Pada Sapi Limousin - Wenny Ladhunka Nur Aliyya; Jakaria Jakaria; Ronny Rachman Noor (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
Abstract Limousin cattle (Bos Taurus) are beef cattle that have a large, long, body shape, with have advantages of fast body growth, high fertility and easy reproducibility. Myostatin gene is a family of TGF-Î² which plays a role in muscle growth and meat quality. This study aims to identify diversity of the Single Nucleotide Polymorphism (SNPs) Myostatine gene in the coding region in limousine cattle. Blood samples were taken from 15 limousine cattle from BPTU-HPT Padang Mangatas, West Sumatra Province. SNPs identification is finish by amplifying the coding region using the sequencing method. This study revealed 12 SNPs spread over 2 SNPs in exon 1 (c.400 G>A, c.415 C>A), 8 SNPs in exon 2 (c.2411 C>T, c.2477 G>A, c. .2489 G>A, c.2503 G>A, c.2521 G>A, c.2577 C>T, c.2609 G>A, c.2636 G>A), and in exon 3 find 2 SNPs (c .5107 C>A, c.5113 T>C) are polymorphic with allele frequencies in general being in Hardy-Weinberg equilibrium except for SNP c.2411 C>T which is not in balance. SNPs identified in the MSTN gene of limousine cattle are expected can fungtion as candidate genetic markers, especially for the perfection of beef cattle in Indonesia. Key words: Limousin Cattle, MSTN, SNP